PENERAPAN MODEL SNOWBAL THORWING UNTUK MENINGKATKAN HASIL BELAJAR TEMA INDAHNYA KERAGAMAN DI NEGERIKU SISWA KELAS IV DISEKOLAH DASAR (Penelitian Tindakan Kelas pada pokok bahasan Tema 7 Sub Tema 2 Kelas IV di Salah Satu Sekolah Negeri di Purwakarta Tahun Ajaran 2020/2021 ) - Khalisa Salsabila, - (2021)
The background of this research is the lack of understanding in social studies learning to find out the improvement of learning outcomes and student activities using the Snoball Throwing model for fourth graders in one of the public elementary schools in Purwakarta for the 2020/2021 academic year. The learning strategy uses the Snowball Throwing model in order to increase student learning outcomes so that students get complete learning outcomes and students become active. The use of this method is the classroom research method with the Spiral Kemmis & Mc Taggart model design, this research has two cycles and there are stages of activities, namely planning, implementation, observation , and reflection. Data that has been obtained through observation and test learning outcomes. The results of the study using the Snowball Throwing model can affect the increase in social studies learning outcomes in grade IV in one of the public elementary schools in Purwakarta, it can be seen from the first cycle who completed 26.66% of learning and finally in the second cycle who completed learning increased to 80.00%.